2008
DOI: 10.1159/000138916
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence of an Association between Norepinephrine Transporter Gene Polymorphisms and Attention Deficit Hyperactivity Disorder

Abstract: Neurobiological and pharmacological research has suggested that dysregulation of the central noradrenergic systems might be involved in the pathophysiology of attention deficit hyperactivity disorder (ADHD). Previous studies have demonstrated that the norepinephrine transporter gene (SLC6A2) is associated with ADHD. The aims of this study were to examine the association of the SLC6A2 G1287A and –3081(A/T) polymorphisms with ADHD in Korean children and adolescents, and to determine the relationships of the geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 66 publications
2
29
2
1
Order By: Relevance
“…This SNP was shown to downregulate the expression of SLC6A2 significantly, representing a very interesting candidate for molecular genetic studies in ADHD. In contrast to the results reported by Kim et al (2006) and Joung et al (2010) and in line with the findings of Cho et al (2008), we did not detect significant transmission disequilibrium for the T-allele in our sample (Kim et al 2006;Joung et al 2010;Cho et al 2008). Our study is based on family data and provides robust results against stratification admixture in contrast to case-control studies.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This SNP was shown to downregulate the expression of SLC6A2 significantly, representing a very interesting candidate for molecular genetic studies in ADHD. In contrast to the results reported by Kim et al (2006) and Joung et al (2010) and in line with the findings of Cho et al (2008), we did not detect significant transmission disequilibrium for the T-allele in our sample (Kim et al 2006;Joung et al 2010;Cho et al 2008). Our study is based on family data and provides robust results against stratification admixture in contrast to case-control studies.…”
Section: Discussionsupporting
confidence: 65%
“…Though Kim et al (2008) further underlined the importance of SLC6A2 in ADHD by an extended association study, the T-3081A variant was not included in the set of investigated variants. In a recent combined case-control and family-based study on Korean children affected by ADHD, Cho et al (2008) were not able to confirm the association for the T-3081A SNP, while Joung et al reported association in a further Korean sample with relatively high odds ratios (Cho et al 2008;Joung et al 2010).…”
Section: Introductionmentioning
confidence: 88%
“…Data were available for meta-analysis from three TDT Brookes et al 2006a;Kim et al 2008) and two Case-Control/HHRR (Cho et al 2008a;Guan et al 2008) studies. Given that no previous studies had reported a signiWcant association between this polymorphism and ADHD, no 'risk' allele was indicated.…”
Section: Norepinephrine Transporter Gene (Slc6a2)mentioning
confidence: 99%
“…Studies have been conducted with a limited number of single-nucleotide polymorphisms (SNPs) within SLC6A2, [21][22][23][24][25] including a functional SNP in the promoter region, [26][27][28] and arrays of tag SNPs covering the entire gene. [29][30][31][32][33] To summarize previous findings and a recent meta-analysis, 34 5 SNPs within SLC6A2 (rs3785157, rs998424, rs3785143, rs11568324, rs28386840) were shown to be associated with ADHD (details provided in Appendix 1, Table S1 and Fig.…”
Section: Introductionmentioning
confidence: 99%